2009
DOI: 10.17221/1723-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Response of larval and juvenile rudd Scardinius erythrophthalmus (L.) to different diets under controlled conditions 331

Abstract: The growth and survival of rudd <I>Scardinius erythrophthalmus</I> (L.) were evaluated in a laboratory at 25°C. In 20-day Experiment 1, first-feeding larvae at the age of 4 days post-hatch (initially: TL = 5.7 mm, BW = 0.9 mg) were fed live <I>Artemia</I> nauplii or commercial dry feed (Aller Futura Larvae, AFL) or combinations of both. Even the longest period of initial feeding of nauplii (6 days) was insufficient to obtain satisfactory larval growth after weaning to AFL (TL = 12.4 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
3
18
1
Order By: Relevance
“…The growth rate of crucian carp in this study was one of the highest than the findings of Daniel et al (2010) who found SCR = 20.06 to 17.38 Woe) in lower stocking density. Kwiatkowski et al (2008), Kujawa et al (2010), Wolnicki et al (2009) A similar survival rate was observed by Daniel et al (2010) ranged from 76.9 to 90.0%. Similar study was conducted by Samad et al (2016); Islam et al (2017); Rahman et al (2017); Rahman et al (2016) and Anka et al (2016); their results were also similar.…”
Section: Discussionsupporting
confidence: 68%
“…The growth rate of crucian carp in this study was one of the highest than the findings of Daniel et al (2010) who found SCR = 20.06 to 17.38 Woe) in lower stocking density. Kwiatkowski et al (2008), Kujawa et al (2010), Wolnicki et al (2009) A similar survival rate was observed by Daniel et al (2010) ranged from 76.9 to 90.0%. Similar study was conducted by Samad et al (2016); Islam et al (2017); Rahman et al (2017); Rahman et al (2016) and Anka et al (2016); their results were also similar.…”
Section: Discussionsupporting
confidence: 68%
“…In case of cyprinids larvae, too short periods of feeding with natural food lead to essential decrease in survival as well as growth rates (Wolnicki, 2005). In the majority of cases, 10 days is enough to prevent the negative effect of compound food offering (Wolnicki, 2005;Wolnicki et al, 2009). In the present study this period influenced positively the survival rate but it turned out not enough to prevent the slowest growth and deformities rate.…”
Section: Discussioncontrasting
confidence: 45%
“…However, the growth rate of larvae of this species is very slow as compared to other cyprinids (i.e. Wolnicki, 2005;Wolnicki et al, 2009), which were able to reach c.a. 25 mm TL during 21 (Wolnicki and Myszkowski, 1999).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Production of stocking material based on reproduction, incubation and rearing under controlled conditions together with improvement of environmental conditions gives a possibility of protection of endangered fish species from river ecosystems Shiri Harzevili et al, 2003Krejszeff et al, 2008Krejszeff et al, , 2009Kucharczyk et al, 2008a,b;Targońska et al, 2008a,b;Żarski et al, 2008a,b;Wolnicki et al, 2009). The rearing of young fish under controlled conditions is the more effective, the more precisely the influence of environmental conditions on the body -relatively sensitive at that time -is determined (Wolnicki, 2005).…”
mentioning
confidence: 99%